The Flipped Classroom Model in German for Hospitality: A Classroom Action Research in The FB Service Study Program - Susianti, Hartanti Woro; Sutama, I Made; Dewantara, I Putu Mas; Wirahyuni, Kadek (Universitas Negeri Makassar, 2025)
Abstract. German language learning at Bali Tourism Polytechnic (BiTP), particularly in reading skills, often faces challenges in effectiveness and student engagement. Students tend to passively receive material in class and lack motivation to develop reading skills independently. This study aims to improve German reading skills and foster independent learning motivation through the Flipped Classroom model. Using Classroom Action Research (CAR), the study examines the model’s application in teaching